Ultrawide field imaging of multiple intraretinal cysts in old rhegmatogenous retinal detachment - Kumar, Vinod (Oman J Ophthalmol, 2016)
A middle ages male presented with old rhegmatogenous retinal detachment with multiple intraretinal macrocysts. Clinical significance of these macrocysts and utility of ultra-wide field imaging in such cases is described.